A preliminary study on mycobiota and ochratoxin a contamination in commercial palm dates (Phoenix dactylifera) - Nikolchina, Iva (2018)
The occurrence of mycotoxins and mycotoxigenic fungi in palm dates has not been thoroughly documented. The aims of the present study were to identify the mycobiota present in commercial date samples (n = 19), to determine the ability of the isolated fungi to produce mycotoxins, and to determine and quantify the presence of OTA in date fruits. The majority of products originated from Tunisia (n = 14) and Algeria (n = 3). The dominant fungal species were Aspergillus niger, Aspergillus tubingensis and Aspergillus flavus which were most frequently found in premium quality and organic produce, produced without chemical preservatives. OTA was found in only one sample at a concentration of 0.75 µg/kg, as determined by HPLC with fluorescence detection. Although this preliminary study did not find elevated levels of OTA, its presence in one out of 19 samples indicates that palm dates for human consumption require continuous and stringent control, in order to prevent contaminated produce from entering the market.